PICTURING EXISTENTIAL FREEDOM IN THE ALCHEMIST - Aditya Nur Cahya; Yeny Prastiwi (Universitas Gunadarma, 2022)
The Alchemist is an adventure novel which highlighted the journey of the main character of this novel, Santiago, a shepherd who endeavored to realize his dream and desire, he who definitely felt at free to pick himself out to where he brings himself to somewhere or being what he had ever desire for his existence. This study focuses on how the depiction of existential freedom is pictured in the novel which is analyzed by existentialist approach. The objective of this study is to mention how existential freedom is pictured in the novel and to analyze the portrayal of existential freedom by the main character of the novel. The study employs document analysis to reveal how Santiago can become a man with freedom that is able to realize his existence, meanwhile in collecting data, the study uses note-taking. This study that applies Sartre’s conception of freedom shows the result that somebody who has their own independency can realize their existence through several stages, which are aware of their existence; aware of their life’s purpose, being in anguish, then them took their choice conscientiously, and committed to themselves for the decisions they had choose nevertheless in the situation which require to change by turns.